THE EFFECTIVENESS OF VILLAGE FUND MANAGEMENT: ACCOUNTABILITY, TRANSPARENCY AND COMMUNITY PARTICIPATION - Ashsifa, Izza; Nur Hidayanti, Alfiyani; Mulyani, Ulva Rizky (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
Government accounting principles, such as accountability, transparency, and participation, are a form of central government, regional, and village obligations. As a government unit directly managing communities with different backgrounds, interests, and needs, the village plays a very important role. In managing village funds, accountability, transparency, and community participation are very important things to do. This study examines and analyzes the effect of accountability and transparency on village fund management in Pati District, with community participation as a moderation variable. This study used research with a quantitative approach. The type of data used in this study is quantitative data. The source of data in this study is primary data. Data collection techniques for this study use survey techniques carried out by distributing questionnaires directly to research respondents. This study used a questionnaire with a Likert Scale model. Structural equation modeling-partial least square (SEM-PLS) tests model hypotheses using SmartPLS. The samples obtained amounted to 300. The respondents in this study were village heads, village secretaries, and village treasurers in Pati Regency. Based on the results of the analysis and hypothesis tests, it proves that accountability and transparency positively affect the effectiveness of village fund management in Pati Regency. This research contributes to the government and community as a reference and evaluation of the government in village fund management. Thus, the budget can empower the community and become information material to optimize community expertise.